Unearthing old rice germplasm, illuminating a new way to improvement - Zheng, Xiaoming; Venuprasad, Ramaiah; Kohli, Ajay (Wiley, 2024)
In summary, this study highlights the effectiveness of mining gene resources from germplasm as a means to overcome current yield limitations in crops. The comprehensive scope of this research, ranging from genetic analysis to cytological observations, chemical mutagenesis, gene cloning, genome assembly, molecular mechanism analysis, breeding evaluations, and even extending to other species, serves as a roadmap for future germplasm exploration. While it was exhilarating to unravel the mystery of CL, we anticipate greater utilization of crop germplasms to discover additional valuable gene resources. These efforts are not only instrumental in enhancing crop improvement, but also contribute to a deeper understanding of fundamental biological processes, as exemplified in this study (Figure 1)